Extraction protocols for individual zebrafish's ventricle myosin and skeletal muscle actin for in vitro motility assays - Scheid, Lisa-Mareike; Weber, Cornelia; Mosqueira, Matias; Fink, Rainer (Frontiers in physiology, 2017)
The in vitro motility assay (IVMA) is a technique that enables the measurement of the interaction between actin and myosin providing a relatively simple model to understand the mechanical muscle function. For actin-myosin IVMA, myosin is immobilized in a measurement chamber, where it converts chemical energy provided by ATP hydrolysis into mechanical energy. The result is the movement of fluorescently labeled actin filaments that can be recorded microscopically and analyzed quantitatively. Resulting sliding speeds and patterns help to characterize the underlying actin-myosin interaction that can be affected by different factors such as mutations or active compounds. Additionally, modulatory actions of the regulatory proteins tropomyosin and troponin in the presence of calcium on actin-myosin interaction can be studied with the IVMA. Zebrafish is considered a suitable model organism for cardiovascular and skeletal muscle research. In this context, straightforward protocols for the isolation and use of zebrafish muscle proteins in the IVMA would provide a useful tool in molecular studies. Currently, there are no protocols available for the mentioned purpose. Therefore, we developed fast and easy protocols for characterization of zebrafish proteins in the IVMA. Our protocols enable the interested researcher to (i) isolate actin from zebrafish skeletal muscle and (ii) extract functionally intact myosin from cardiac and skeletal muscle of individual adult zebrafish. Zebrafish tail muscle actin is isolated after acetone powder preparation, polymerized, and labeled with Rhodamine-Phalloidin. Myosin from ventricles of adult zebrafish is extracted directly into IVMA flow-cells. The same extraction protocol is applicable for comparably small tissue pieces as from zebrafish tail, mouse and frog muscle. After addition of the fluorescently labeled F-actin from zebrafish—or other origin—and ATP, sliding movement can be visualized using a fluorescence microscope and an intensified CCD camera. Taken together, we introduce a method for functional analysis in zebrafish cardiac and skeletal muscle research to study mutations at the molecular level of thick or thin filament proteins. Additionally, preliminary data indicate the usefulness of the presented method to perform the IVMA with myosin extracted from muscles of other animal models.